2020
DOI: 10.3390/jpm10040210
|View full text |Cite
|
Sign up to set email alerts
|

Association of UBE3C Variants with Reduced Kidney Function in Patients with Diabetic Kidney Disease

Abstract: Diabetic kidney disease (DKD) is the leading cause of morbidity and mortality in patients with diabetes mellitus (DM) and the most common variant of end-stage renal disease (ESRD) globally. The economic burden of ESRD treatment with dialysis is substantial. The incidence and prevalence of ESRD in Taiwan remain the highest worldwide. Therefore, identifying genetic factors affecting kidney function would have valuable clinical implications. We performed microarray experiments and identified that ubiquitin protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For instance, ubiquitin ligase E3C (UBE3C) is differentially expressed in DKD patients and diabetes patients without chronic kidney disease. One study intends to illustrate that UBE3C can reduce renal function in DKD patients [28]. In addition, Arkadia was significantly increased in diabetic kidneys and induced Smad7 ubiquitination degradation, which suggested that inactivation of the Arkadia-Smad7 ubiquitin-proteasomal degradation pathway may be a key mechanism [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ubiquitin ligase E3C (UBE3C) is differentially expressed in DKD patients and diabetes patients without chronic kidney disease. One study intends to illustrate that UBE3C can reduce renal function in DKD patients [28]. In addition, Arkadia was significantly increased in diabetic kidneys and induced Smad7 ubiquitination degradation, which suggested that inactivation of the Arkadia-Smad7 ubiquitin-proteasomal degradation pathway may be a key mechanism [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue, Functional Genomics and Pharmacogenomics in Human Disease, covers 15 publications conducted by various groups, including nine original research papers, five review papers, and one case report. Original research papers consist of genetic discovery and functional characterization of CYP1A2 and CYP2C9 [ 1 , 2 ], genetic studies of oral cancer [ 3 , 4 , 5 ], chronic obstruction pulmonary disease (COPD) [ 6 ], asthma [ 7 ], diabetic kidney disease [ 8 ], and web-based pharmacogenomics tool development [ 9 ]. Review papers include the thiopurine treatments with NUDT15 polymorphisms [ 10 ], lipid lowering therapies in familial hypercholesterolemia [ 11 ], incorporation of genetic addiction risk severity (GARS) to overcome the addiction pandemic [ 12 ], and the latest update on genetic variants of UGT [ 13 ] and SULT genes [ 14 ].…”
mentioning
confidence: 99%
“…Diabetic kidney disease (DKD) occurs mainly in diabetic mellitus patients and is the most common form of end-stage renal disease (ERSD). A microarray experiment was conducted and found that the ubiquitin protein ligase E3C (UBE3C) is a candidate gene that affects kidney function [ 8 ]. Then, it was reported that the UBE3C haplotype with the identified variants was correlated with chronic kidney disease.…”
mentioning
confidence: 99%